Hemostatic Evaluation With Viscoelastic Coagulation Monitor: A Nicu Experience - Amelio, Giacomo Simeone; Raffaeli, Genny; Amodeo, Ilaria; Gulden, Silvia; Cortesi, Valeria; Manzoni, Francesca; Pesenti, Nicola; Ghirardello, Stefano; Mosca, Fabio; Cavallaro, Giacomo (Frontiers in Pediatrics, 2022)
Background: Viscoelastic coagulation tests provide valuable information in neonatal intensive care units (NICUs), but the lack of reference intervals still limits their decision-making power according to gestational age. The aim of the present study is to evaluate the hemostasis of a cohort of full-term (FT) and late-preterm (LP) infants using the viscoelastic coagulation monitor (VCM®) system, a new portable device that uses untreated whole blood. Methods: An observational study was performed to identify non-coagulopathic FT and LP infants admitted to III° level NICU (January 2020 to December 2021) with a VCM test in the first 72 hours of life. Results: Forty-five patients were enrolled, 26 FT and 19 LP. No statistical differences in hemostatic parameters were observed between FT and LP nor between stable and unstable neonates. Clotting time (CT) was positive correlated with PT (p=0.032), not with aPTT (p=0.185). From linear regression, platelet resulted associated with: clot formation time (CTF, p=0.003), alpha angle (Alpha, p=0.010), amplitude at 10 (A10, p=0.001), aplitude at 20 minutes (A20, p<0.001), maximum clot firmness (MCF, p<0.001); and fibrinogen was associated with: A10 (p=0.008), A20 (p=0.015) and MCF (p=0.024). Compared to the adult reference population, neonates showed shorter CT (mean (SD): 5.3 (1.4) vs. 7.0 (0.9) minutes, p<0.001), CFT (2.4 (0.7) vs. 2.8 (0.6) minutes, p<0.001) and higher Alpha (60.8 (6.3) vs. 55 (5)°, p<0.001). In addition, the neonatal cohort showed an early transient difference in amplitude and fibrinolysis, as follows: A10 (28.0 (5.0) vs. 26 (4) VCM units, p =0.004), A20 (34.8 (5.0) vs. 33 (4) VCM units, p =0.012), and LI30 (99.8 (0.5) vs. 99 (1)%, p <0.001). Conclusions: The viscoelastic profile of FT and LP infants assessed with VCM showed a hemostatic competence characterized by accelerated coagulation and clot formation time, in line with other viscoelastic techniques. VCM system provides promising applications in the NICU setting.